Effect of the low-frequency turbulence on the aeroelastic response of a long-span bridge in wind tunnel. Issue 197 (February 2020) - Argentini, Tommaso; Rocchi, Daniele; Somaschini, Claudio
Abstract: The influence of the low frequency turbulence components on the buffeting response of long span bridges was studied through experimental tests performed on a full bridge aeroelastic model in the wind tunnel of the Politecnico di Milano, using an active turbulence generator producing a correlated deterministic harmonic turbulence. The experimental evidence underlined the nonlinear effect of the low frequency incoming turbulence on the dynamic resonant response of the structure at higher frequencies. Numerical simulations are used to explain the bridge behavior considering the variation of the aeroelastic properties of the bridge with the instantaneous angle of attack and reduced velocity. Even though wind tunnel experiment uses an oversimplified wind spectrum with an intentionally high correlation along the main span, it helps to understand the nonlinear interaction between the low frequency and the high frequency buffeting response on a full bridge. Highlights: An experimental case of the nonlinear low-frequency turbulence effects on the aeroelastic response of a full-bridge model. A simplified bi-harmonic wind spectrum is considered to better highlight the nonlinear effects. The low-frequency variation of the angle of attack makes the response switching between stable and unstable conditions. A band superposition model is used to explain the experimental behavior, relying on standard aerodynamic coefficients.